BUSINESS DIGITALIZATION: AN ISLAMIC BUSINESS ETHICS PERSPECTIVE WITH THE BMC MODEL - Tati Handayani; Sufyati HS; Anggi Angga Resti; Silvia Dewi Sagita Andik (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2025)
The growth of MSMEs plays an important role in the Indonesian economy, but many still face limitations in utilizing digital technology. This study analyzes the batik business model using the BMC approach combined with Islamic business ethics. Data were obtained through interviews, observations, and literature review. The study shows that Islamic principles are applied concretely through transparency in production and transaction processes, fairness in wage distribution, and healthy competition through product differentiation and public education. The analysis also found challenges in the form of limited digital marketing skills, dependence on raw materials from outside the region, and a lack of regeneration of young craftsmen. The recommended strategies are strengthening digital channels, diversifying products, developing partnerships with educational and tourism institutions, and enhancing the capacity of the younger generation. These strategies not only support business sustainability but also reinforce the integration of economic innovation with moral responsibility in accordance with Islamic values.